The Relationship of Digital Literacy with The Help of Anyflip.com to The Learning Motivation of Elementary School Students - Meidawati Suswandari; Jauhan Budiwan; Abdah Munfaridatus Sholihah (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
The research objective is to determine the relationship between Digital Literacy assisted by Anyflip.com on the Learning Motivation of Class IV students at SDN Buran 03 Karanganyar. The method of collecting research data is quantitative. The total population is 132 students. Meanwhile, the study sample was 29 fourth-grade students with information obtained from data collection tools in questionnaires and documentation. The research data analysis was consulted with the prerequisite analysis test, then continued on the scale validity test using the product-moment correlation. The research concludes that the relationship between digital literacy assisted by Anyflip.com on the learning motivation of fourth-grade students at SDN Buran 3 Karanganyar is significant. Decision-making is based on the product-moment test, namely r arithmetic > r table 0.632 > 0.3009, so that Ha is accepted and Ho is rejected. This fact means that the use of digital literacy assisted by anyflip.com is not only digital information obtained by students, but students can explore, create, and be more active in online learning so that educational interactions occur between students and teachers.